Topical cyclosporine A 1 mg/ml for atopic keratoconjunctivitis: Five‐year case series of 99 children and young people. Issue 2 (23rd September 2022) - Dahlmann‐Noor, Annegret H.; Roberts, Clare; Muthusamy, Kirithika; Calder, Virginia; Hingorani, Melanie
Abstract: Purpose: To explore the effects of cyclosporine A (CsA) in the management of atopic keratoconjunctivitis (AKC). Methods: Open single‐group interventional consecutive cohort study (case series) at a single eye care facility in the UK. We reviewed the electronic patient records of 99 children and young people (CYP) aged 3.4–18 years with AKC treated with topical CsA 1 mg/ml. Main outcome measures were number of prescriptions and hospital clinic visits over 12 months before and after the start of CsA and the proportion of CYP affected by adverse effects. Results: The median number of inflammatory episodes requiring treatment with topical corticosteroids (tCS) fell from 3 (interquartile range IQR 1–4) during the 12 months prior to CsA to 1 (IQR 0–3) during the 12 months after, excluding tCS prescriptions with the first CsA prescription (Wilcoxon signed ranks test, 2 tailed, p  < 0.01). In the 12‐month period following initiation of CsA 1 mg/ml with concomitant prescription of tCS ( n  = 66), daily dosage of steroids was reduced in 62 CYP (93.9%), and they were discontinued in 43 (65.2%). The median number of hospital visits fell from 4 (IQR 3–6) to 3 (IQR 2–5; Wilcoxon p  < 0.01). Adverse events leading to discontinuation of CsA were stinging (instillation site pain; 9/99, 9%) and a transient skin rash (1/99, 1%). Conclusions: Off‐label use of commercial preparations of CsA 1 mg/ml significantly reduces the need for concomitant topical corticosteroids and hospital clinic visits in CYP with AKC. Stinging and skin rash can lead to discontinuation.